A herbivore tag-and-trace system reveals contact- and density-dependent repellence of a root toxin - Bont, Zoe; Arce, Carla; Huber, Meret; Huang, Wei; Mestrot, Adrien; Sturrock, Craig; Erb, Matthais (Springer, 2017)
Foraging behavior of root feeding organisms strongly affects plant-environment-interactions and ecosystem processes. However, the impact of plant chemistry on root herbivore movement in the soil is poorly understood. Here, we apply a simple technique to trace the movement of soil-dwelling insects in their habitats without disturbing or restricting their interactions with host plants. We tagged the root feeding larvae of Melolontha melolontha with a copper ring and repeatedly located their position in relation to their preferred host plant, Taraxacum officinale, using a commercial metal detector. This method was validated and used to study the influence of the sesquiterpene lactone taraxinic acid β-D-glucopyranosyl ester (TA-G) on the foraging of M. melolontha. TA-G is stored in the latex of T. officinale and protects the roots from herbivory. Using behavioral arenas with TA-G deficient and control plants, we tested the impact of physical root access and plant distance on the effect of TA-G on M. melolontha. The larvae preferred TA-G deficient plants to control plants, but only when physical root contact was possible and the plants were separated by 5 cm. Melolontha melolontha showed no preference for TA-G deficient plants when the plants were grown 15 cm apart, which may indicate a trade-off between the cost of movement and the benefit of consuming less toxic food. We demonstrate that M. melolontha integrates host plant quality and distance into its foraging patterns and suggest that plant chemistry affects root herbivore behavior in a plant-density dependent manner. © 2017, Springer Science+Business Media New York.